GLOBAL GOVERNANCE VS. NATIONAL SOVEREIGNTY IN A GLOBALIZED WORLD - Sabina TUCA (CES Working Papers, 2015)
The global economic and financial crisis of 2007 highlighted the risks, threats and enormous costs of a global economy in the absence of a global government. The aim of this paper is to emphasize the importance of global governance in a world in which states are facing the erosion of national sovereignty. The two concepts are being analyzed from various points of view, including current challenges and future scenarios. Despite the fact that states, especially major powers, are not prepared to accept some elements of global governance and the limits that they would put on their national sovereignty, recent developments seem to make global governance a key component of the international scene.